2021
DOI: 10.3390/app112210585
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Shear Strength of Reinforced High-Strength Concrete Beams Using Compatibility-Aided Truss Model

Abstract: This study proposes an analytical model applicable to the shear analysis of reinforced high-strength concrete beams. The proposed model satisfies the equilibrium and compatibility conditions and constitutive laws of the materials. The proposed model is based on the fixed angle theory and allows the principal stress to rotate as the load increases, so that the RC beams can be analyzed more realistically. High-strength material models were used in the proposed model to consider the characteristics of high-streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several design guidelines and codes exist worldwide (fib Task group 5.1, 2019; ACI Committee 440, 2017; Construction C-AC on TR for. CNR-DT 200 R1/2013, 2013TR-55 CSTR, 2012;JSCE Japanese Society of Civil Engineers, 2000;Abuodeh et al, 2020;Ly et al, 2020;Chalioris et al, 2020;Benzeguir and Chaallal, 2021;Kim, 2021;Isleem et al, 2021). The lack of consensus is due to the following reasons:…”
Section: Introductionmentioning
confidence: 99%
“…Several design guidelines and codes exist worldwide (fib Task group 5.1, 2019; ACI Committee 440, 2017; Construction C-AC on TR for. CNR-DT 200 R1/2013, 2013TR-55 CSTR, 2012;JSCE Japanese Society of Civil Engineers, 2000;Abuodeh et al, 2020;Ly et al, 2020;Chalioris et al, 2020;Benzeguir and Chaallal, 2021;Kim, 2021;Isleem et al, 2021). The lack of consensus is due to the following reasons:…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental [6][7][8][9][10], numerical [11][12][13] and theoretical works [14][15][16][17][18][19][20] have been carried out to examine flexural ductility of single-span reinforced HSC members. A few researchers have also evaluated the shear [21] and torsional behavior [22,23] of single-span reinforced HSC members. Previous research showed that in spite of the brittleness of HSC, reinforced HSC members with reasonably arranged steel bars exhibited favorable ductile ability.…”
Section: Introductionmentioning
confidence: 99%